AB0453 Presentation and management of granulomatosis with polyangiitis (wegener's) (gpa) central nervous system (cns) involvement. (23rd January 2014) - De Luna, G.; Terrier, B.; Charles, P.; Pagnoux, C.; Puéchal, X.; Cohen, P.; Mouthon, L.; Guillevin, L.
Abstract : Background: GPA, a small-sized–vessel vasculitis, commonly involves ear, nose & throat (ENT), lungs and kidneys, and rarely, the CNS. Objectives: The presentation, management and outcome of GPA CNS involvement were evaluated. Methods: We retrospectively reviewed the charts of 16 patients (12 men) with: GPA satisfying ACR and/or Chapel Hill criteria; and, after excluding other causes, GPACNS involvement manifesting as pachymeningitis, meningitis, stroke, spinal cord involvement or hypophyseal involvement. Results: Mean respective ages at GPA diagnosis and onset of CNS involvement were 43 and 47 years. The latter was present in 9 (56%) patients at GPA diagnosis, and appeared in the 7 others after a median follow-up of 24 months. Headache was the main symptom (67%), with motor and sensory impairments noted in 33 and 27%, respectively. CNS involvements were: pachymeningitis (n=8: 7 cranial and 1 spinal cord), ischemic (n=4) or hemorrhagic stroke (n=2), cerebral vasculitis (n=2), and/or hypophyseal involvement (n=2). Extra-CNS manifestations included ENT (75%), lungs (60%), peripheral nerve(s) (40%) and kidneys (33%). ANCA detected in 12/16 (75%) patients had PR3 (n=7) or MPO (n=5) specificity. Induction therapy comprised corticosteroids (CS, 100%) and IV (69%) or oral cyclophosphamide (CYC, 25%) or rituximab (6%). Maintenance therapy consisted of CS (100%) and azathioprine (63%), or methotrexate or rituximab (13% each). CNS involvement responded clinically in 12/16 (75%). Relapsing and/or refractory CNS GPA in 7 patientswas treated with IV CYC or rituximab (43% each) or oral CYC (14%). No patient died during follow-up, but 64% had persistent neurologicalsequelae. Conclusions: Our series highlights the heterogeneity of CNS involvement in GPA. Despite initial severe disease, conventional therapy obtained clinical improvement in 75% of the patients. Rituximab should be evaluated for refractory and/or relapsing CNS GPA. Disclosure of Interest: None Declared